Live Not by Lies: A Man ual for Christian Dissidents. Rod Dreher = Žyty ne za nepravdoju: posibnyk dlja chrystyjansʹkych dysydentiv. Rod Drejer - Matsyuk, Vasyl (Bogoslovs'ki rozdymi, 2021)
Live Not by Lies: A Man ual for Christian Dissidents. Rod Dreher.New York, U.S: Sentinel, 2020, 256 PP.; ISBN 9780593087398;27.00 USD